Pathogenic Mechanisms of Trimethylamine N-Oxide-induced Atherosclerosis and Cardiomyopathy - Zheng, Youjing; He, Jia-Qiang (Current Vascular Pharmacology, 2022)
Trimethylamine N-oxide (TMAO) is a gut microbiota metabolite derived from trimethylamine- containing nutrient precursors such as choline, L-carnitine, and betaine, which are rich in many vegetables, fruits, nuts, dairy products, and meats. An increasing number of clinical studies have demonstrated a strong relationship between elevated plasma TMAO levels and adverse cardiovascular events. It is commonly agreed that TMAO acts as an independent risk factor and a prognostic index for patients with cardiovascular disease. Although most animal (mainly rodent) data support the clinical findings, the mechanisms by which TMAO modulates the cardiovascular system are still not well understood. In this context, we provide an overview of the potential mechanisms underlying TMAO-induced cardiovascular diseases at the cellular and molecular levels, with a focus on atherosclerosis. We also address the direct effects of TMAO on cardiomyocytes (a new and under-researched area) and finally propose TMAO as a potential biomarker and/or therapeutic target for diagnosis and treatment of patients with cardiovascular disease.
Keywords: cardiomyopathy